The IoT-Based E-Voting System Using Fingerprint Biometrics for School Elections - Wibowo, Wahyu Andre; Ujianto, Erik Iman Heri (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
This study proposes an Internet of Things (IoT)-based e-voting system to address the limitations of traditional paper-based student council elections, which are prone to errors, inefficiency, and data manipulation. The system is developed using the ADDIE model for Research and Development (R&D), incorporating a Laravel-based administrative dashboard, a Flutter-based mobile voting interface, and a biometric authentication device built with an ESP32 microcontroller and JM-101B fingerprint sensor. Evaluation involved 20 participants who completed six functional test scenarios, achieving a 100% success rate across 120 instances. Usability testing revealed a notable comfort difference, with 30% comfort on mobile phones and 90% on tablets. Performance testing showed a fingerprint scan time of 669.6 ms and a vote submission latency of 437.1 ms, indicating good system responsiveness. The results suggest the system improves security, transparency, and efficiency in the election process. However, the study is limited by a small sample size and evaluation within a single institution. Future work could explore cloud integration, multi-school deployment, and additional authentication methods to enhance scalability and support broader adoption.